THE USE OF THEMATIC PROGRESSION TO IMPROVE THE COHERENCE OF THE STUDENTSâ WRITINGS - Mulatsih, Sri (ETERNAL, 2010)
Abstract To produce good writings, the students need to know how to organize Theme and Rheme in their writings to make their writings coherent. This organization of Theme and Rheme is known as Thematic Progression. This classroom action research was conducted to know whether Thematic Progression really improved the coherence of the studentsâ writings. The population in this research consisted of 104 second semester students taking Paragraph-Based Writing course in 2008-2009 academic year at English Department, Faculty of Languages and Letters, Dian Nuswantoro University. They were given a treatment about Thematic Progression. After receiving this treatment, they were asked to write English paragraphs using certain paragraph development, and the results were evaluated. The cycle was iterated for three times. The sample of this research was taken randomly using purposive random sampling. FortyÂ students were taken as the sample, especially those who had the complete marks for the whole cycles. The result showed the significant improvement on the coherence on the studentsâ writingsÂ indicated by the increased mean scores in every cycle. The thematic progression pattern the students mostly employed in developing their paragraphs is theme reiteration. The second preferred is zig-zag pattern, while multiple pattern was rarely employed in their writings. Key words: Coherence, Rheme, Studentsâ writings, Thematic Progression patterns, Theme.